A Handlist of Illustrated Early Solomonic Manuscripts in British Public Collections - Karlsson, Jonas; Gnisci, Jacopo; Dege-Müller, Sophia (Aethiopica, 2023)
As material objects bearing textual and visual information, illustrated Christian manuscripts from the Horn of Africa are among the most valuable sources of data for scholars specializing in this field. This article is the second handlist produced within the framework of the AHRC-DFG project Demarginalizing medieval Africa: Images, texts, and identity in Early Solomonic Ethiopia (1270– 1527). It focuses on illustrated Early Solomonic manuscripts housed in public libraries in the United Kingdom. This is the first time that this body of illuminations has been comprehensively analysed. The resulting work sheds new light on the history of book illustration in Early Solomonic Ethiopia and provides insights into the connected histories of the Christian empire of the Ethiopian-Eritrean highlands and the wider Mediterranean world. Moreover, it showcases the movements of manuscripts and the development of collections of Gǝʿǝz manuscripts in Europe.